Nanoparticles (NPs) in aquaculture industry: current status and future perspectives - Rakhi, RF; Shahariar, MA; Alam, MS (Annals of Bangladesh Agriculture, 2022)
The fastest-growing aquaculture industry plays a crucial role in fulfilling the increased demand for animal protein. However, the outcomes of the sectors are greatly hindered by unexpected disease prevalence, environmental degradation, organic and inorganic pollutants in aquaculture operations, and ineffective feed exploitation to achieve the global food security goal. There has been little research on the impact of nanotechnology on fish nutrition and improved health, despite the fact that the application of nanotechnology in food production systems is being studied globally. In this respect, scientists are generating and inventing new potential ideas and technology to cope with these challenges in aquaculture. Among them, the use of nanoparticles (NPs) has grown in popularity due to their numerous attractive and distinctive features and also tremendous potential to improve aquaculture production. New ideas regarding the application of NPs in fish medicine, drug delivery techniques through NPs, diet formulation to enhance feed efficacy, and as an antiviral or antimicrobial agent to control disease prevalence in aquaculture systems to augment overall production have been discussed. Commercially cultured fish species, including shrimp, Thai koi, Common carp, Grass carp, and Tilapia, have been shown to respond favorably to a variety of nanoparticles (eg. silver, gold, iron, copper, zinc, selenium, and chitosan). Thus nanoparticles researched-based information in finfish and shellfish aquaculture have short-term or long-term prospects and can be used as a potential candidate for nanomedicines combined with fish feed. These new ideas can be studied further before being utilized commercially in the aquaculture fish feed industries and it has huge merit in the future aquaculture need to be considered. Ann. Bangladesh Agric. (2022) 26 (1) : 113-125